ANALISIS POTENSI KONTRIBUSI RETRIBUSI TERMINALTERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MIMIKA Yahya Nusa *1 - Yahya Nusa; Marthinus Batkunda (CV. Adiba Aisha Amira, 2024)
The potential to increase Regional Original Income by drafting regulations relating to regional levies, namely regulations regarding terminal levy rates and conducting studies to find out how much terminal levies contribute to Regional Original Income as well as carrying out trend analysis to predict how many years to come. The research was conducted using qualitative and quantitative descriptive methods. Based on the results of the analysis, what was found was that the results of terminal levy collections obtained using the calculation of potential terminal levies and adjusted to the tariff increases stated in the Regent's Regulations obtained greater results compared to the billing system currently being implemented and trend projections showed that there was an increase in levies. terminal every year for the next five years.